FLIPPED-BASED LEARNING FOR EFL STUDENTS: ENHANCING CLASSROOM INTERACTION AND AUTONOMY IN THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) - Fassya, Intan Fachri; Zulaiha, Siti; Mulyono, Herri; Rosita, Riskha (English Review: Journal of English Education, 2025)
This study investigates the impact of flipped learning on classroom interaction and student autonomy among secondary school EFL students involved in the Pancasila Student Profile Strengthening (P5) project. A mixed-methods design was used, integrating both quantitative and qualitative data to gain a deeper understanding of the research questions. Data were collected through a survey and interviews. The survey, completed by 536 students, assessed students’ perceptions of flipped learning using the adapted Technology Acceptance Model (TAM). Data analysis was conducted using Rasch analysis, which helped identify outliers and assess the reliability of the survey instrument. Qualitative data, gathered from interviews with 10 students, were analyzed thematically to explore how flipped learning influenced students’ classroom interaction and autonomy. The findings indicate that flipped learning improves both classroom interaction and student autonomy, although challenges related to technology access and adapting to independent learning were noted. These insights offer valuable guidance for educators and curriculum developers aiming to implement flipped learning effectively in secondary education.